Designing Pop Up Book Media Using ADDIE Model to Enhance Understanding of Asmaul Husna in Akidah Akhlak for Madrasah Ibtidaiyah Students - Fauziah, Nadia Nurul; Calian, Yayan; Muhamadi, Sani Insan; Saefuddin, Asis (LJPI UI Bunga Bangsa Cirebon, 2025)
The purpose of the study was to determine the design developed, validation of experts on product feasibility and differences in understanding after using Pop Up Book media. The method used is R&D (Research and Development) ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used questionnaires, tests, interviews and documentation. Data analysis uses descriptions for qualitative data, and uses statistics for quantitative data. The results of the study based on data analysis obtained Pop Up Book learning media that have been made and validated by media experts get an average of 83.9%, linguists get 78.5%, material experts get 84%, Akidah Akhlak teachers get 94% and student responses on a small scale get an average of 93.75%. The results of validation and response get the “Worthy” category to be tested. The results of the understanding of grade V MI Ciharalang students before using Pop Up Book get a percentage of 47.2%, after using Pop Up Book media, student understanding gets a percentage of 83.3%. Based on the results of the study, it can be concluded that the Pop Up Book media is suitable for use as a learning medium and can improve student understanding in grade V MI Ciharalang.